Human Centred AI for Inclusive Microfinance: A Data Driven Model for Women’s Credit Empowerment and Macroeconomic Upliftment - Chaudhary, Vishal Kumar; Suman, Sumit; Kumari, Sneha (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Artificial Intelligence (AI)-powered microfinance framework has been specifically designed to cater for the needs of women in rural India. The model integrates microeconomic behaviour analytics, macroeconomic simulation using Computable General Equilibrium (CGE) models, and machine learning techniques like Random Forest and Extreme Gradient Boosting (XGBoost) to recommend optimal loan amounts, assess credit risk, and predict empowerment outcomes. By leveraging empirical evidence from global and Indian contexts—including Self Help Group (SHG) case studies, Financial Technology (FinTech) innovation, and algorithmic fairness tools—this framework aims to enhance women’s transparency, inclusion, and long-term socio-economic upliftment. There has been an emphasis on practical applicability, interpretability, and policy relevance for inclusive financial systems.